The importance of formic acid excretion in the urine for environmental and occupational medicine questions - Schmid, K; Schaller, K H; Angerer, J; Lehnert, G (Zentralblatt für Hygiene und Umweltmedizin, 1994)
The suitability of the formic acid excretion in the urine as a parameter for the biological monitoring of inhalational exposure to formaldehyde is discussed controversially. We investigated persons not occupationally exposed to formaldehyde (n = 70) to determine possible influencing factors on the physiological excretion of formic acid. Following this we carried out a study on medical students (n = 30), who during an anatomical dissection course were exposed to a short but intensive inhalational exposure to formaldehyde, as well as investigations on employees of a pathological-anatomical laboratory (n = 8) in order to observe the course of the formic acid excretion in the urine during a working week with a continuous exposure to formaldehyde below or within the range of the MAK value (0.5 ppm). It was seen that the formic acid excretion in the urine with non-exposed persons is subject to considerable inter and intraindividual fluctuations (at a maximum by a factor of 30). In addition to differences in the endogenous formation of formates an important influencing factor is probably the uptake of food containing formic acid or its precursors. A value of 23 mg formic acid/g creatinine is given as the upper norm level (95th percentile) of adults. In the groups who were exposed to formaldehyde, in some cases considerably above the MAK value, we were able to detect no significant increase in the formic acid concentration in the urine. After a short but intensive exposure to formaldehyde (0.32-3.48 ppm) the formic acid concentration in the urine did not change significantly with an average formic acid concentration in the urine before exposure of 6.5 mg/g creatinine (central 50% range: 3.5-14.2 mg/g creat.) and after exposure of 6.0 mg/g creatinine (central 50% range: 4.4-10.9 mg/g creat.). There was no significant relationship between the individual change in the formic acid concentration in the urine (in mg/g creatinine) and the inhalational exposure to formaldehyde determined through personal air sampling (r = 0.079). In the course of a working week with a continuous exposure to formaldehyde (0.03-0.83 ppm) there was after relating the values to creatinine a continuous increase in the median to 22.3 mg/g creat. with a starting value of 8.7 mg/g creat. The change proved, however, for the number of cases investigated not to be significant. In particular there was no linear correlation detectable between the individual changes in the formic acid excretion in the urine and the formaldehyde concentrations in the breathing zone determined by personal air sampling.